POTRET KONFLIK KEAGAMAAN MASYARAKAT TANGERANG BANTEN DAN RESOLUSI KONFLIK BERBASIS MULTIKULTURALISME DALAM ISLAM - Ulfah Fajarini (AL-TAHRIR, 2014)
Conflicts still occur invariably in Indonesia although their volumes are lesser than the previous decade. However, their patterns and causes are largely still the same, in which the issues of religion, religious celebration or observation and theology are predominant. This article aims to explore sources of social conflict between the community members affiliating with Nahdlatul Ulama (NU) and those of Muhammadiyah. It examines the triggering factors and the patterns of the conflict.  It also analyzes the processes of this conflict resolution which are based on the concept of multiculturalism in Islam. The data of this anthropological study were collected through both interviews and observasion and are analyzed qualitatively. This study shows the roots of the social conflict between the members of Nahdlatul Ulama and Muhammadiyah revolved around the issues of religious celebration, rituals and epistemic interpretation. Stigmatization, misunderstanding and exclusivity often stimulated the conflict. The concept of Islamic multicultularism must be implemented to manage Muslim internal religious relations especially in Tangerang, Banten, to settle such conflicts.